Insurance in an islamic economy - Siddiqi, Muhammad Nejatullah (United Kingdom : The Islamic Foundation, 1985)
Social science
2004-11-02
Keywords: Insurance; Islamic economy; Insurance i Islamic countries; Islamic systems; Islamic countries